If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -3 = 10x + -10 Reorder the terms: -3 + 3y = 10x + -10 Reorder the terms: -3 + 3y = -10 + 10x Solving -3 + 3y = -10 + 10x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3y = -10 + 3 + 10x Combine like terms: -3 + 3 = 0 0 + 3y = -10 + 3 + 10x 3y = -10 + 3 + 10x Combine like terms: -10 + 3 = -7 3y = -7 + 10x Divide each side by '3'. y = -2.333333333 + 3.333333333x Simplifying y = -2.333333333 + 3.333333333x
| (-13y^9+6)-(-4y^9)=0 | | x-10=2x-34 | | 4x-9x=13-63 | | 3(5x-6)=42 | | 7x+6=-5x | | 5x+7(x+1)+3=10-6x | | x-.2x=1300 | | 0.16(5x-2)=0.4x+17 | | 122-2x=16x+20 | | w^5x^4y^5-wxy=0 | | 77.50=.15x+10 | | -12a^6+8a^3=0 | | 18x^3-60x^2=-50x | | 12x*x^2=0 | | 6x-8=82 | | 3x+21=63 | | 187-5x=40x+22 | | 16x^2-24x+9=13 | | 12x*1x^2=0 | | 12x*1x^2=x | | 2x*1x^2=0 | | 2x*1x^2=x | | 3x^2+5x-18=0 | | 99-3x=4x | | 10x^2+31x-14=0 | | 4m^2+3m=1 | | b+2.35=9.78+2b+7.22 | | v^2-9v-10=0 | | 4a-12b+20a= | | m^2+9m+18=0 | | 4h^2-4h+1=0 | | e^2-5e-84=0 |